Insights on Light Dispersion in Semi‐Alicyclic Polyimide Alignment Layers to Reduce Optical Losses in Display Devices. Issue 12 (8th October 2018) - Barzic, Andreea Irina; Hulubei, Camelia; Stoica, Iuliana; Albu, Raluca Marinica
Abstract: Two polyimide structures are prepared from an alicyclic dianhydride and aromatic diamines, containing or lacking fluorine. The polymer films are characterized for display technology purposes. Light dispersion data of the studied samples are compared with those of some nematics to evaluate optical losses in the liquid crystal cell. It is shown for the first time that matching refractive indices of polyimide and nematic at several wavelengths is essential for reduction of Fresnel reflections, thus improving the device performance. Resistivity measurements indicate that rubbing generates a few surface charges on the surface of the fluorine‐derived polymer, which contribute to a more uniform orientation of liquid crystals, as supported by polarized microscopy analysis. Both pristine polyimide films exhibit a smooth surface with isotropic features, which are changed into anisotropic ones after rubbing, as a consequence of microgrooves' appearance. Their thickness uniformity is affected by the structure of the diamine moieties. The adhesion of all nematics to the polyimide films is enhanced by the rubbing procedure. Abstract : Light dispersion in semi‐alicyclic polyimides is investigated to evaluate optical losses in the liquid crystal cell. For the first time, it is evidenced that matching refractive indices of polyimide and nematic at several wavelengths is essential for reduction of Fresnel reflection and enhancing display performance. The fluorinated polyimide exhibits uniform orientation of the liquid crystal being suitable as alignment layer.